2016
DOI: 10.1136/bmjopen-2016-012351
|View full text |Cite
|
Sign up to set email alerts
|

Towards the genetic basis of cerebral venous thrombosis—the BEAST Consortium: a study protocol

Abstract: IntroductionCerebral venous thrombosis (CVT) is a rare cerebrovascular condition accounting for <1% of all stroke cases and mainly affects young adults. Its genetic aetiology is not clearly elucidated.Methods and analysisTo better understand the genetic basis of CVT, we have established an international biobank of CVT cases, Biorepository to Establish the Aetiology of Sinovenous Thrombosis (BEAST) which aims to recruit highly phenotyped cases initially of European descent and later from other populations. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 42 publications
0
28
0
Order By: Relevance
“…Several protocols have been used with the purpose of maintaining healthy cognitive functions (Cotlarciuc et al, 2016; Brem and Sensi, 2018). In a recent study, Ware et al (Ware et al, 2017) have shown that computer-assisted learning of a second language leads to social and motivational benefits, although they did not investigate different cognitive domains.…”
Section: Discussionmentioning
confidence: 99%
“…Several protocols have been used with the purpose of maintaining healthy cognitive functions (Cotlarciuc et al, 2016; Brem and Sensi, 2018). In a recent study, Ware et al (Ware et al, 2017) have shown that computer-assisted learning of a second language leads to social and motivational benefits, although they did not investigate different cognitive domains.…”
Section: Discussionmentioning
confidence: 99%
“…Additional mechanical risk factors for CVST include neurosurgery, internal jugular catheterization and lumbar puncture . Regarding genetic causes, several loci on chromosome 6 (within the human histocompatibility complex) and chromosome 9 (close to the ABO gene) have been involved in the development of CVST , although these associations remain to be confirmed in large genome‐wide association studies . The association of CVST with other candidate genes, such as plasminogen activator inhibitor‐1 4G/5G polymorphism and protein Z G79A polymorphism , remains controversial.…”
Section: Risk Factorsmentioning
confidence: 99%
“…The genetic basis of CVT is widely unknown and has gained attention as a research question because nearly 10% to 25% of cases have no identifiable risk factors. 1,6,7 Certain gene candidates have been studied as the main genetic risk predisposition for CVT; unfortunately, due to the difficulty in achieving a sufficient sample size, multiple studies have failed to show a causative association. Factor V Leyden (G1691A polymorphism), 8 prothrombin mutation (G20210A polymorphism), 8 methylene tetrahydrofolate reductase (C677T polymorphism), 9 plasminogen-activator inhibitor-1 (4G/4G polymorphism), 10 protein Z (G79A polymorphism), 11 Janus kinase-2 (V617F polymorphism), 12 and thrombin-activatable fibrinolysis inhibitor (TAFI; A505G, C1040T, and C1542G polymorphisms) 13 are a subset of the genes possibly associated with risk of CVT development.…”
Section: Introductionmentioning
confidence: 99%